Sutureless circumcision - An Indian experience - Punit Tiwari; Astha Tiwari; Suresh Kumar; Rajkumar Patil; Amit Goel; Pramod Sharma; Anup K Kundu (Indian Journal of Urology, 2011)
Context: Traditionally, circumcision wounds are closed by absorbable sutures. However, certain alternative methods are also being utilized to overcome the shortcomings of the conventionally used method for circumcision wound closuring. In the current study, the use of tissue glue ((iso amyl 2-cyanoacrylate) has been compared with traditional suturing for the approximation of circumcision wounds. In our study, both the methods were found to be comparable with significantly less time consumed in glue group. Aims: The purpose of the present study has been to compare directly cyanoacrylate as a better alternative to conventional suture material in terms of cosmetic result, time consumed and incidence of infection (comparative study). Materials and Methods: The results of all the patients seen in outpatient department for circumcision were included in this study. The study was conducted from Aug 2009 to May 2010. The tissue glue (iso amyl 2-cyanoacrylate) was compared to sutures as a method of wound approximation in circumcision. Results: Tissue glue group has been observed to have less wound inflammation, bleeding or hematoma rate and was cosmetically superior as compared to suture group; however, none of these findings could reach statistically significant level. The mean time taken for circumcision was 14.2 min (SD 2.42), when tissue glue was used for wound approximation. However, it was 24.4 min (SD 5.06) in case of the use of sutures. This difference was found as highly significant (P value < 0.001). However, regarding postoperative pain no significant reduction was observed when glue was used. Conclusions: This study showed that the use of tissue glue in comparison to sutures is having the following advantages: Cosmetically superiorLess time consuming All other parameters measured were nearly the same and statically insignificant.